Case Report: A case of synchronous multiple early gastric cancer with a microsatellite instability-high phenotype - Xinshuo Wang; Yifan Zhang; Guangyan Fan; Honglei Wu; Xing Qi; Xiujie Cui; Chengjun Zhou (Frontiers in Oncology)
Synchronous multiple early gastric cancer (SMEGC) is a relatively uncommon variant of early gastric cancer (EGC). In this report, we present a case of SMEGC accompanied by a microsatellite instability-high (MSI-H) phenotype. The patient was a 69-year-old man who presented to our hospital with abdominal pain. The endoscopic examination revealed two lesions. Both lesions were pathologically confirmed as EGC, then the patient subsequently underwent endoscopic submucosal dissection (ESD). Nine months post-procedure, the patient returned with recurrent abdominal pain, leading to the diagnosis of a new EGC. Immunohistochemical analysis demonstrated that all lesions exhibited an MSI-H phenotype and BRAF mutant expression, suggesting that these lesions are not associated with Lynch syndrome-related EGC. The case was ultimately diagnosed as SMEGC with an MSI-H phenotype. The current evidence and clinical experience suggest that patients with advanced MSI-H are likely to benefit from immunotherapy and should be considered for early systemic treatment with immunotherapy as a central component. At present, research studies on the molecular characteristics of SMEGC are limited, underscoring the importance of conducting comprehensive molecular diagnostics of each EGC patient, which could help clinicians thoroughly understand the lesion’s characteristics.